High-intensity gas seepage causes rafting of shallow gas hydrates in the southeastern Black Sea. - Pape, Thomas; Bahr, André; Klapp, Stephan A; Abegg, Friedrich; Bohrmann, Gerhard (PANGAEA, 2011)
Submarine gas hydrates are a major global reservoir of the potent greenhouse gas methane. Since current assessments of worldwide hydrate-bound carbon vary by one order of magnitude, new technical efforts are required for improved and accurate hydrate quantifications. Here we present hydrate abundances determined for surface sediments at the high-flux Batumi seep area in the southeastern Black Sea at 840 m water depth using state-of-the art autoclave technology. Pressure sediment cores of up to 2.65 m in length were recovered with an autoclave piston corer backed by conventional gravity cores. Quantitative core degassing yielded volumetric gas/bulk sediment ratios of up to 20.3 proving hydrate presence. The cores represented late glacial to Holocene hemipelagic sediments with the shallowest hydrates found at 90 cmbsf. Calculated methane concentrations in the different cores surpassed methane equilibrium concentrations in the two lowermost lithological Black Sea units sampled. The results indicated hydrate fractions of 5.2% of pore volume in the sapropelic Unit 2 and mean values of 21% pore volume in the lacustrine Unit 3. We calculate that the studied area of ~ 0.5 km**2 currently contains about 11.3 kt of methane bound in shallow hydrates. Episodic detachment and rafting of such hydrates is suggested by a rugged seafloor topography along with variable thicknesses in lithologies. We propose that sealing by hydrate precipitation in coarse-grained deposits and gas accumulation beneath induces detachment of hydrate/sediment chunks. Floating hydrates will rapidly transport methane into shallower waters and potentially to the sea-atmosphere boundary. In contrast, persistent in situ dissociation of shallow hydrates appears unlikely in the near future as deep water warming by about 1.6 °C and/or decrease in hydrostatic pressure corresponding to a sea level drop of about 130 m would be required. Because hydrate detachment should be primarily controlled by internal factors in this area and in similar hydrated settings, it serves as source of methane in shallow waters and the atmosphere which is mainly decoupled from external forcing.
Hydrate abundances at the high-flux Batumi seep area in the southeastern Black Sea
Keywords: Batumi_seep_Backscatter_area; Batumi_seep_sampled_area; Batumi Seep; Batumi seep area; Center for Marine Environmental Sciences; DAPC; DAPC-1; DAPC-12; DAPC-14; DAPC-15; DAPC-3; DAPC-8; DAPC-9; Dynamic autoclave piston corer; GeoB11901; GeoB11906; GeoB11918; GeoB11920; GeoB11937; GeoB11951; GeoB11958; M72/3a; M72/3b; MARUM; Meteor (1986); MULT